Crecimiento de la «palometa» Parona signata (Jenyns, 1842) Berg, 1895 (Pisces, Carangidae) - San Roman, Nemesio Amaro (1976)
Five hundred specimens of Parona signata known as «palometa» in the South Atlantic (Mar del Plata) were studied as a part of more extensive biological investigations. The relations between lenght/age, lenght/weight, weight/age and condition factor are given. The correlation (r) was high in all cases. The maximal age in males was 6 years, with lenghts between 43 cm and 51 cm; in females the maximal ase was 6 years with lenght between 44 cm and 59 cm.